2023
DOI: 10.1128/jmbe.00168-22
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizations and Limitations of STEM Literacy across Learning Theories

Abstract: The concept of literacy is relevant in many areas of life, both inside and out of the classroom. With science, technology, engineering, and math (STEM) being fast-growing fields, STEM literacy in particular holds an important place in today’s education system and beyond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, for a topic as complex as scientific literacy, how do you determine which framework is appropriate for your particular take on scientific literacy? Tenney et al identified three different learning theories, information processing, constructivism, and sociocultural theory, and they discussed the conceptualizations of science, technology, engineering, and math (STEM) literacy and offered insightful perspectives on how to conceptualize what it means to be STEM literate ( 1 ). And, if you envision science literacy to be larger than these three theories, and to extend outside of the classroom, Elhai here helps readers redefine science literacy at the community level ( 2 ).…”
Section: Editorialmentioning
confidence: 99%
“…However, for a topic as complex as scientific literacy, how do you determine which framework is appropriate for your particular take on scientific literacy? Tenney et al identified three different learning theories, information processing, constructivism, and sociocultural theory, and they discussed the conceptualizations of science, technology, engineering, and math (STEM) literacy and offered insightful perspectives on how to conceptualize what it means to be STEM literate ( 1 ). And, if you envision science literacy to be larger than these three theories, and to extend outside of the classroom, Elhai here helps readers redefine science literacy at the community level ( 2 ).…”
Section: Editorialmentioning
confidence: 99%
“…The essence of each discipline must be emphasized (Huang et al, 2023). Students' STEM literacy growth will be correlated to improved communication and literacy skills (Joyner & Parks, 2023;Tenney et al, 2023). However, according to Nugroho et al (2019), Rochman et al (2019), and van Laar et al (2020), STEM is frequently perceived as difficult, and many students leave science, technology, engineering, and mathematics (STEM) courses.…”
Section: Introductionmentioning
confidence: 99%